ความร่วมมือระหว่างหน่วยงานรัฐและองค์กรพัฒนาเอกชน ในสถานคุ้มครองสวัสดิภาพผู้เสียหายจากการค้ามนุษย์ - เกษริน กันทะอินทร์ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The research of Government Agencies and Non-government Organisations Collaboration in Welfare Protection Center for Victims of Trafficking in Persons (TIP) has the objectives : 1) To study the collaboration among a government agencies and related non-government organizations (NGOs) in working for the protection of the beneficiaries (victims) from The Welfare Protection Center for Victims of Trafficking in Persons (TIP); 2) To study the challenges of such collaboration in order to identify recommendation for the development of appropriate collabpration in working for the protection of the beneficiaries (victims) from The Welfare Protection Center for Victims of Trafficking in Persons (TIP). This research employed the qualitative method whereas the researchtools included semi-structured interview, participatory & non-participatory observations, as well as reviews of related literatures. The research’s 9 key informants were sampled, using purposive sampling method, among directors and staffs from different shelters under the administration of The Welfare Protection Center for Victims of Trafficking in Persons (TIP), as well as NGO workers from related NGOs working with these shelters. Results of this study indicates the following factors of cooperation: 1) The common goal and aim set by both parties, government agencies and non-government organizations, involved is in the best interests of the beneficiary (victim); 2) Innovative and multiplex problem-solving developed; 3) Trust (among government agencies and non-government organizations) built from working duration, which shows a positive growth in relationship; 4) Authority, decision making, vision and perspective of administrative officers play an important role in cooperation; 5) Development potential in cooperation and reciprocation between government agencies and nongovernment organizations identified; 6) Two methods of communication including official and unofficial developed whereas unofficial communication usually results in more flexibility and interaction; 7) Cooperative monitoring and evaluation developed which were mostly organized as debriefing meetings, though there is no observance in overall takeaways. Furthermore, there were positive changes that occurred within government agencies, which include: 1) Using recommendations from NGOs to modify the organization’s services towards beneficiaries (victims); 2) Instilling a positive attitude amongst government officials towards beneficiaries (victims); 3) Instilling new knowledge and vision amongst government officials; 4) Implementing more flexibility in operations through mutual understanding, and adapting plans to increase effectivity. Challenges that were faced include: 1) Lack of continuity in cooperation, resulting in NGOs working based on project agreement and funding while frequent staff turn-over within government agencies and The Welfare Protection Center for Victims of Trafficking in Persons (TIP); 2) Government officials do not have a clear code of conduct for working with NGOs, resulting in ambiguity within decision-making, often resting on the final decision from government administrators; 3) Lack of NOGs’ involvement in reviewing overall takeaways or lesson learnt of The Welfare Protection Center for Victims of Trafficking in Persons (TIP); 4) Lack of a central networking database, which could be utilized to analyze and follow cooperation between and government officials and NGO workers in servicing beneficiaries (victims); 5) NGOs were not involved in authority and decision-making powers over policy implementation, which is only reserved to government officials. The solutions towards these challenges include: 1) Implementing a mutual understanding, common goal, and organized responsibility between government agencies and NGOs; 2) Implementing long-term mutual share of resources. 3) Allowing NGOs to be more involved in government policy making. 4) Organizing review meetings to observe overall takeaways or lesson learnt from working among The Welfare Protection Center for Victims of Trafficking in Persons (TIP), Anti-Human Trafficking of Thailand and NGOs; 5) Organizing unofficial (informal) cooperative events that promote equity.